Investigating Organizational Determinants of Job Satisfaction: Mediating Role of Motivation - Tjanturi, Sehan; Sulistyaningsih, Endang; Ho, Shu-Hsun (Journal of Entrepreneurship and Business, 2024)
Purpose: The objective of this research is to examine the influence of Organizational Climate and Perceived Organizational Support on Job Satisfaction, with Motivation acting as a mediating variable among Digital Agency Workers in Indonesia. Method: The study involved disseminating questionnaires to 76 employees across three digital agency firms located in the Jakarta Metropolitan Area, Indonesia, utilizing the convenience sampling method. The analysis of the collected data was performed through Structural Equation Modeling (SEM) using the Smart PLS 4 software. Result: The study's findings indicate that Organizational Climate and Perceived Organizational Support exert a direct influence on Job Satisfaction and on Motivation. Moreover, it was discovered that Motivation serves as a mediating factor in the relationship between Organizational Climate and Job Satisfaction, as well as between Perceived Organizational Support and Job Satisfaction. The author stresses the need for future research to focus on various external factors when analyzing job satisfaction. This includes factors such as personality traits, economic conditions, and challenges specific to certain industries.